Systematic Literature Review (SLR) Peran Asuransi Syariah dalam Membantu Perkembangan UMKM - Ghofur, Umrotul (Jurnal Ekonomi Aktual, 2024)
This article discusses the role of Islamic insurance in assisting the development of small and medium enterprises (UMKM). Islamic insurance has two contracts, namely Tijarah and Tabarru'. As part of efforts to support the development of UMKM, Islamic insurance introduces a new innovation, which is Tabarru' mutual assistance between UMKM participants and the insurance party. The profit will be shared because it is done by the insurance party, which uses the principle of Shariah. In Islamic insurance there is also Tijarah which also provides benefits to UMKM, and in Islamic insurance there is already Halal guarantee by the Indonesian Council of Ulama (MUI) through the fatwa DSN (National Shariah Council with Fatwa No. 21/DSN-MUI/X/2001 on general guidelines for Islamic insurance. The method used in this research is the Systematic Literature Review (SLR) by Bettany-Saltiknov (2012) by summarizing findings from previous relevant studies. Therefore, topics considered relevant to this research will be discussed, criticized, and concluded.